RESPONSIBILITY PT ASTRA DENGAN PEMERINTAH DAERAH PASANGKAYU DI DESA MARTAJAYA - Siti Anisah; Denis Tirtana; Nur Adha K Husen3; Jonathan Aldovel; Putri Asti Sidik; Risty Indah Sari; Rachmad, S.Sos., M,Si. (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Collaboration between the private sector and local government is a crucial tool in accelerating community welfare development at the village level. This study aims to analyze the implementation of PT Astra's Corporate Social Responsibility(CSR) programs in synergy with the Pasangkayu Regency Government and their impact on community development in Martajaya Village. The research employed a qualitative descriptive analysis approach. Information was obtained through in-depth interviews with PT Astra management, local government officials, village officials, and community leaders inMartajaya Village, supported by documentation studies. The study revealed that the synergy of responsibilities between PT Astra and the Pasangkayu Regional Government in Martajaya Village focuses on four main pillars: village infrastructure development, strengthening the local potential-based economy,increasing healthcare accessibility, and providing educational scholarships. This collaboration is considered successful in covering the shortfall in the regional budget (APBD). However, this study also identified challenges in the form of the need for more dynamic coordination to ensure program implementation is more sustainable and avoids overlapping. The study's conclusions confirm that effective collaboration between companies and the local government can have a significant positive impact on the independence of the Martajaya Village community.